Advanced finite element modeling of excavation and advancement processes in mechanized tunneling. (October 2016) - Alsahly, Abdullah; Stascheit, Janosch; Meschke, Günther
Highlights: A computational framework for modeling curved tunnel advancement is proposed. A steering-correction algorithm for the advancement of the TBM is developed. The continuous excavation process is modeled using adaptive remeshing. All relevant interactions between tunnel construction and the soil are considered. Abstract: Mechanized tunneling is characterized by complex interactions between the shield machine and the surrounding ground during the TBM advancement process. In this paper, a new computational framework is developed to enable an efficient and realistic three-dimensional modeling of the tunneling process for arbitrary alignments using the finite element method. A new steering algorithm for the advancement of the Tunnel Boring Machine (TBM) for arbitrary alignments during shield tunneling is incorporated in the proposed model. This algorithm simulates the shield behavior and accordingly provides the numerical model with the required information to keep the TBM on track during the simulation. However, the utilization of this algorithm is only possible using a finite element discretization which adapts to the actual motion path of the shield machine. For this purpose, a re-meshing technique is proposed in order to automate the process of mesh generation in the vicinity of the tunnel face, denoted as the region of interest, within the advancing process. The combination of a computational steering algorithm and a 3D automatic adaptive mesh generation procedure form a novel framework for process oriented finite element simulations of the mechanized tunnel construction process. The applicability of the proposed modeling technique for predicting the shield behavior and the soil-tunnel interactions during tunneling along curved alignments is demonstrated by means of selected examples.